Identification of Power System Oscillation Modes Using Empirical Wavelet Transform and Yoshida-Bertecco Algorithm - Philip, Joice G.; Yang, Yejin; Jung, Jaesung (IEEE Access, 2022)
Oscillations occurring in the power system are one of the biggest threats to its secure operation. Although they occur rarely, these oscillations can cause severe damage to the power system if they are not detected at the earliest. Hence, this work focuses on identifying the parameters of oscillations in the power system using a combination of Empirical Wavelet Transform and Yoshida-Bertecco algorithm. As these oscillations occur rarely, a preprocessing method based on Teager Kaiser Energy Operator is used to check whether the signal under consideration contains any oscillation modes. The effectiveness of the proposed method is tested using a test signal, simulated power system signal, and PMU data from an actual power system under various levels of noise contamination. Further, the performance of the proposed method is compared with a VMD-Hilbert transform-based, Prony-based, and SSI-based methods in the literature. Results reveal the superiority of the proposed method irrespective of the parameters of the signal under consideration.
Keywords: Empirical wavelet transform; Energy operators; Mode decomposition; Power; Power system; Power system oscillations; Prony’; S-method; Signal processing algorithms; Stochastic subspace identification; Teager kaiser energy operator; Variational mode decomposition; Wavelet-analysis; Wavelets transform; Empirical wavelet transform; power system oscillations; Prony's method; stochastic subspace identification; Teager Kaiser energy operator; variational mode decomposition